2011
DOI: 10.1002/jcb.23175
|View full text |Cite
|
Sign up to set email alerts
|

Activation of EGFR promotes squamous carcinoma SCC10A cell migration and invasion via inducing EMT‐like phenotype change and MMP‐9‐mediated degradation of E‐cadherin

Abstract: EGFR is a potent stimulator of invasion and metastasis in head and neck squamous cell carcinomas (HNSCC). However, the mechanism by which EGFR may stimulate tumor cell invasion and metastasis still need to be elucidated. In this study, we showed that activation of EGFR by EGF in HNSCC cell line SCC10A enhanced cell migration and invasion, and induced loss of epitheloid phenotype in parallel with downregulation of E-cadherin and upregulation of N-cadherin and vimentin, indicating that EGFR promoted SCC10A cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
171
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(186 citation statements)
references
References 46 publications
15
171
0
Order By: Relevance
“…2A). The constitutive expression of EGFR in metastatic tumor cells has previously been demonstrated to be associated with enhanced MMP-9 expression and induction of invasive capacity (25). In the present study, it was observed that CXCR4-overexpressing cells elevated MMP-9 production compared with controls (Fig.…”
Section: Cxcr4 Promotes Expression Of Egfr and Elevates Mmp-9 Productsupporting
confidence: 69%
See 1 more Smart Citation
“…2A). The constitutive expression of EGFR in metastatic tumor cells has previously been demonstrated to be associated with enhanced MMP-9 expression and induction of invasive capacity (25). In the present study, it was observed that CXCR4-overexpressing cells elevated MMP-9 production compared with controls (Fig.…”
Section: Cxcr4 Promotes Expression Of Egfr and Elevates Mmp-9 Productsupporting
confidence: 69%
“…In the Transwell migration assay, as previously described (21,25), the underside of the Transwell insert (pore size, 8 µm; Costar; Corning Incorporated, Corning, NY, USA) was pre-coated with collagen type I (Col-I, 1 µg/ml) or fibronectin (10 µg/ml). Subsequently, 2x10…”
Section: Antibodiesmentioning
confidence: 99%
“…Zhou et al (2014) showed that suppression of EGFR by miRNA-7 is able to inactivate the ERK-1/2/ATK signaling cascade, thus reversing EMT and attenuating metastasis in epithelial ovarian cancer cells. Zuo et al (2011) found that EGFR activation can induce EMT-like phenotype change and MMP-9-mediated degradation of E-cadherin in HNSCC SCC10A cells through the ERK-1/2 and PI3K signaling pathways. Based on these findings, the negative effects of LRIG1 on EMT are most likely attributed to inactivation of the EGFR/PI3K/AKT pathway triggered by the antagonistic interaction between EGFR and LRIG1, consequently suppressing VM formation and VM-dependent malignant behaviors in glioma cells (the hypothetical scheme is shown in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Wang et al indicated that overexpression of activated Erk1/2 and cyclin D1 proteins are involved in oral tongue carcinogenesis (51). Finally, Judd et al (59) reported that MEK1 activation enhances CD44 expression and promotes aggressiveness in HNSCC, while Katada et al (60) and Zuo et al (61) suggested that Erk1/2 activation correlates with increased cell migration and invasion in HNSCC.…”
Section: Discussionmentioning
confidence: 99%